Pengaruh Pembelajaran Kewirausahaan dan Lingkungan Sosial Terhadap Minat Berwirausaha Mahasiswa Program Studi Pendidikan Administrasi Perkantoran UNS - Ahmad Khairuddin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this research is to: 1) determine an influence of entrepreneurial learning on the entrepreneurial interest of students in the UNS Office Administration Education study program; 2) determine an influence of the social environment on the entrepreneurial interest of students in the UNS Office Administration Education study program; and 3) determine an influence of entrepreneurial learning and the social environment together on the entrepreneurial interest of UNS Office Administration Education students. This research uses a quantitative approach with correlational methods. The population in this research is all students from the 2019 and 2020 Office Administration Education Study Program, totaling 113 students. This research uses a proportional stratified random sampling technique for sampling. The data analysis in this research uses multiple linear regression analysis techniques with the help of the IBM SPSS 24.0 program. The research results show that: 1) there is a positive influence of entrepreneurial learning on interest in entrepreneurship as evidenced by the calculated t value (1.712) > t table (1.658). 2) there is a positive influence of the social environment on interest in entrepreneurship as evidenced by the calculated t value (2.099) > t table (1.658). 3) there is a positive influence of entrepreneurial learning and the social environment together on interest in entrepreneurship as evidenced by the value of Fcount (6.287) > Ftable (3.08). The research results also show that entrepreneurial learning and the social environment together can influence interest in entrepreneurship by 10.3%, while the other 89.7% is influenced by other variables. Therefore, the overall results of this data analysis support the existing hypothesis.